Materials for the flora of Nova Kakhovka Ordinary Fish Hatchery (NP "Oleshkivski sands") (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The annotated list of vascular plants of the one of the part of National Park "Oleshkivski sands" – the territory of Nova Kakhovka Ordinary Fish Hatchery – is presented. Flora of this area, which is about 200 hectares, has 197 species of vascular plants of 159 generas, 49 families and 4 departments. On the territory of Ordinary Fish Hatchery there are 7 rare vascular plant species which are included in the IUCN Red List, the European Red List, Red Data Book of Ukraine and Red List of Kherson region.
Keywords: flora, vascular plants, Nova Kakhovka Ordinary Fish Hatchery, conservation.